SUBTITUSI PAKAN KONVENSIONAL DENGAN PAKAN NON-KONVENSIONAL PADA SATWA TARSIUS (Tarsius dianae) YANG DIPELIHARA DALAM KANDANG - Yulius Duma; Abdul Rosyid; Mobius Tanari; Mardiah Mangun; Damry Damry (Biocelebes, 2023)
This research was conducted in order to know the conventional feed of tarsier could be substituted by non-conventional feed such as fish and chicken. The research showed that the conventional feed could be susbstituted with fish and chicken without annoying the comfortable of tarsier’s life.